Behavior of Ceria as an Actinide Surrogate in Electro-Slag Remelting and Refining Slags - U B. Pal (The Minerals, Metals and Materials Society, 2002)
Downsizing and decommissioning of nuclear facility operations is increasing the stockpile of various different grades of Radioactive Scrap Iron (RSI). Disposal of this material not only represents significant resource and value lost, but also necessitates long term monitoring for environmental compliance. The latter results in additional recurring expense. It is desirable to be able to decontaminate the RSI to a very low level that can be recycled or used for fabrication of containers for RSI disposal instead of using virgin metal to fabricate the container. Electro-Slag Remelting and Refining (ESR) is often used for decontaminating radioactive contaminated sources of scrap iron such as stainless steel. Non-radioactive oxides of cerium are used to simulate the radioactive oxide contaminants of Uranium and Plutonium. The success of the ESR process is strongly dependent on the capacity of the slag to rapidly incorporate the radioactive contaminant (simulant). In this study we have measured the slag-metal partition coefficient for cerium and investigated the reaction mechanism for the dissolution CeO, in the slag.